NPInter v4.0: an integrated database of ncRNA interactions. Issue Volume 48:Issue D1(2020) (31st October 2019) - Teng, Xueyi; Chen, Xiaomin; Xue, Hua; Tang, Yiheng; Zhang, Peng; Kang, Quan; Hao, Yajing; Chen, Runsheng; Zhao, Yi; He, Shunmin
Abstract: Noncoding RNAs (ncRNAs) play crucial regulatory roles in a variety of biological circuits. To document regulatory interactions between ncRNAs and biomolecules, we previously created the NPInter database (http://bigdata.ibp.ac.cn/npinter ). Since the last version of NPInter was issued, a rapidly growing number of studies have reported novel interactions and accumulated numerous high-throughput interactome data. We have therefore updated NPInter to its fourth edition in which are integrated 600 000 new experimentally identified ncRNA interactions. ncRNA–DNA interactions derived from ChIRP-seq data and circular RNA interactions have been included in the database. Additionally, disease associations were annotated to the interacting molecules. The database website has also been redesigned with a more user-friendly interface and several additional functional modules. Overall, NPInter v4.0 now provides more comprehensive data and services for researchers working on ncRNAs and their interactions with other biomolecules.